Digital Transformation: Elevating Landscape Architecture through Building Information Modeling (BIM) - Weldy Eka Saputra; Lee Yoke Lai; Fatema Malas Nafeed (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
Building Information Modelling (BIM) is widely used in architecture and construction, particularly in building and structure design. However, BIM is imposed in landscape architecture design, which is still not much applied in landscape architecture, academically and practically. Therefore, this paper explores the benefits of BIM application in landscape architecture design. A methodology involves a systematic literature review (SLR) on BIM landscape architecture to explore the purposes and benefits of BIM's landscape architecture. The study found that the BIM application has contributed valuable benefits to the landscape architecture design process and the digital modeling of landscapes. Moreover, the study provides a solution software application and tool to generate a sustainable landscape design from the pre-design stage of landscape architecture projects . In short, successfully utilizing BIM depends on an operator's human skills to use the application in landscape architecture projects and enhance the multiple aspects of landscape visualization.